Barriers and facilitators to physical activity participation among community-dwelling physically inactive individuals after stroke: A qualitative exploratory study - YOLCU, GÜNAY; KENİŞ COŞKUN, ÖZGE; ÇİFÇİLİ, SALİHA SERAP (My University, 2024)
Physical activity has been shown to reduce the risk for first-ever stroke as well as recurrent stroke with positive effects on almost all known modifiable risk factors. However, the perceived barriers and facilitators for engaging in physical activity have been insufficiently studied and may differ between cultures. Therefore, the aim of this study was to explore the perceptions of community-dwelling physically inactive individuals with stroke about barriers and facilitators to their participation in physical activity. This qualitative study included two focus groups of ten individuals with stroke classified as physically inactive based on accelerometer recordings. A semi-structured set of questions was posed in each focus group session and the transcripts were analysed using thematic analysis. The results revealed three main themes and subthemes: individual factors (physical impairments, psychological factors, spirituality), interaction with the family (attitudes of family members/close community) and social and environmental factors (hobbies, lack of or presence of facilities, the use of orthosis). We conclude that physical activity participation is affected by a multitude of factors as well as cultural differences. Thus, interventions aimed at increasing participation in physical activity after stroke should not only be planned according to individual clinical characteristics but also take into account a range of personal-to-social factors, including cultural differences.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; physical activity; qualitative research; rehabilitation; stroke